TUBERCULOUS AZOOSPERMIA - A CASE REPORT - GBESSI, GASPARD DANSOU; HOUNNASSO, PRINCE PASCAL; NATCHAGANDE, GILLES; DOSSOU, FRANCIS MOÏSE DJIDÉNOU; AVAKOUDJO, JOSUÉ DEJINNIN GEORGES; MEHINTO, KUASSI DELPHIN; AKELE ÉPOUSE AKPO, MARIE THÉRÈSE M.; OLORY-TOGBE, JEAN-LÉON TOUSSAINT (My University, 2013)
This a case report of an immunocompetent (HIV negative) 54 years old man who had been diagnosed with epididymo-testicular tuberculosls. This happened 13 years after he had suffered from pulmonary tuberculosi.s. The diagnosls was made after a testicular biopsy for infertility. Theoutcome of anti-tuberculosistreatmentw.as good although the azoospermia lasted. The aim of this report is to emphasize that the genital tuberculosis still exists in our sub-region and that high index of suspicion is required with effective anti-
Keywords: Urogenital tuberculosis; Azoospermia; infertility; Benin Republic